The South Shetland Islands, Antarctica: Lithostratigraphy and geological map - Bastías, Joaquín; Chew, David; Villanueva, Camila; Riley, Teal; Manfroi, Joseline; Trevisan, Cristine; Leppe, Marcelo; Castillo, Paula; Poblete, Fernando; Tetzner, Dieter; Giuliani, Gregory; López, Bastián; et al. (Frontiers in Earth Science, 2023)
Over the last few decades, numerous geological studies have been carried out in the South Shetland Islands, which have greatly contributed to a better understanding of its geological evolution. However, few attempts have been conducted to correlate the geological units throughout this archipelago. We present herein a lithostratigraphical correlation, which constitutes a coherent and unified stratigraphy for the main Mesozoic and Cenozoic units rocks of the South Shetland Islands along with a new geological map. The lithostratigraphical correlation shows that the geological evolution comprises three main stages: (i) deep marine sedimentation from ~164 to 140 Ma, (ii) subaerial volcanism and sedimentation with a proliferation of plants and fauna from ~140 to 35 Ma and (iii) glacial and interglacial deposits from ~35 Ma. The lithostratigraphical correlation also shows a broad geographical trend of decreasing age of volcanism from southwest to northeast, which has been previously suggested. However, this spatial age trend is disrupted by the presence of Eocene magmatism in Livingston Island, located in the centre of the archipelago. We suggest that the migration of volcanism occurred from the Late Cretaceous until the early Eocene. Subsequently, enhanced magmatic activity took place from the mid-Eocene until the Miocene, which we associate with processes related with the waning of subduction, such as roll-back. Finally, constraining the protolith age of the metamorphic complex of Smith Island remains challenging, yet holds key implications for the tectonic and accretionary evolution of the Antarctic Peninsula. The rocks recording the glaciation of this sector of Antarctica are well exposed in the northern South Shetland Islands and hold critical information for understanding the timings and processes that lead to the greenhouse-icehouse transition towards the Eocene end. Contemporaneous rocks to the breakup of Antarctic Peninsula from Patagonia, which led to the Drake Passage opening and the development of the Scotia Sea, are exposed in the north-centre of the archipelago. A better age constrain of these units may lead to further understanding the paleontological evolution of this region. The dataset containing the geological map is shared as a shapefile and KML file.